2005
DOI: 10.1007/bf02702014
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and trace element chemistry of the siliceous earth of barmer basin, Rajasthan: Evidence for a volcanic origin

Abstract: We report the presence of a 3-5 cm thick loose fragmental layer in the Siliceous Earth at Matti ka Gol in the Barmer basin of Rajasthan. Petrographic, chemical and mineralogical study reveals the presence of abundant volcanic debris such as glass shards, agglutinates, hollow spheroids, kinked biotites, feldspars showing oscillatory zoning, olivines, ilmenite and native iron. The presence of similar particles in the whole section suggests that the Siliceous Earth is a volcanic ash. Stratigraphic correlation, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…The Mangala and Aishwarya/Aishwariya oil fields have been producing hydrocarbons from the Barmer Hill Formation (Shiju et al 2008;Lobo et al 2015). Figure 2 presents a Wheeler diagram of a chronostratigraphic section, taking into account the available stratigraphic information from current literature (Sisodia and Singh 2000;Mathur 2003;Mathur et al 2005;Sisodia et al 2005;Compton 2009;Beaumont et al 2015;Dolson et al 2015;Kothari et al 2015).…”
Section: Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…The Mangala and Aishwarya/Aishwariya oil fields have been producing hydrocarbons from the Barmer Hill Formation (Shiju et al 2008;Lobo et al 2015). Figure 2 presents a Wheeler diagram of a chronostratigraphic section, taking into account the available stratigraphic information from current literature (Sisodia and Singh 2000;Mathur 2003;Mathur et al 2005;Sisodia et al 2005;Compton 2009;Beaumont et al 2015;Dolson et al 2015;Kothari et al 2015).…”
Section: Geologymentioning
confidence: 99%
“…The MIS is a heterogeneous group of three-phased ig- Figure 2. Chronostratigraphic NW-SE section across the Barmer basin (compiled from Sisodia and Singh 2000;Mathur 2003;Mathur et al 2005;Sisodia et al 2005;Compton 2009;Dolson et al 2015;Kothari et al 2015;John et al 2017). Major depositional units with respect to geological time associated with prominent erosional events and hiatuses are presented.…”
Section: Geologymentioning
confidence: 99%
“…In the outcrop, a "Siliceous Earth" had already been reported and described as a soft, porous, homogeneous and low density rock (Sisodia et al, 2005), although the available evidence led these authors to suggest a volcanic origin for the unit. In the current study, equivalent representative outcrop samples of the Barmer Hill Formation have been analysed using SEM and XRD methods.…”
Section: Structural Setting and Geological Characterisationmentioning
confidence: 99%
“…However, more evidence is required to support this suggestion. Sisodia et al (2005) reported a 3-5 cm thick loose fragmental layer in siliceous earth from the Barmer basin, comprising volcanic debris such as glass shards, agglutinates, hollow spheroids, kinked biotites, feldspars, olivines, ilmenite and native iron. They suggested that the bands of siliceous earth were volcanic ash deposited during the Upper Cretaceous to Lower Paleocene.…”
Section: Barmer Basinmentioning
confidence: 99%